PERLINDUNGAN HUKUM TERHADAP KURATOR TERKAIT FEE/IMBALAN JASA DALAM MELAKSANAKAN PROSES GOING CONCERN KEPAILITAN - Irwandi Husni; Nur Hakim; Roni Pandiangan (SINERGI : Jurnal Riset Ilmiah, 2025)
In bankruptcy practice, not all bankrupt assets can be immediately liquidated, because Law Number 37 of 2004 opens opportunities for debtors who are still economically prospective to continue their business (going concern ). The purpose of going concern  is to maintain asset value, maximize debt payments, and reduce socio-economic impacts, with judge supervision and creditor approval. However, there is still a legal vacuum regarding the protection of curator service Fees for additional risks and workloads. The formulation of the research problem is: how is the legal regulation of the implementation of going concern  in bankruptcy, and how is the legal protection for curators related to Fees/service Fees in carrying out the process of continuing the debtor's business (going concern ) in bankruptcy. The theory used is Satjipto Rahardjo's legal protection and M. Hadi Shubhan's bankruptcy theory. The method used in this research is a normative juridical research, namely library legal research or secondary data with primary, secondary, and tertiary legal materials as sources. The research approach used is a legislative approach, a conceptual approach, and legal material collection techniques are carried out by identifying and inventorying positive legal regulations, literature books, journals, and other legal material sources. The legal material analysis technique is carried out using grammatical legal interpretation, systematic interpretation, teleological interpretation, and functional interpretation. The results of the study indicate that legal protection for curators in going concern  cases is inadequate. Clear legal regulations are needed regarding the mechanism for implementing going concern  cases, including the regulation of compensation for curators in carrying out going concern  cases. It is recommended that Law Number 37 of 2004 be revised, as well as the Regulation of the Minister of Law concerning Guidelines for the Amount of Remuneration for Curators and Administrators, and that intensive training related to the implementation of going concern  cases be conducted by the Ministry of Law of the Republic of Indonesia to improve the capacity of curators in managerial, financial, and business governance aspects